Effect of Breadmaking Process on In Vitro Gut Microbiota Parameters in Irritable Bowel Syndrome - Costabile, Adele; Santarelli, Sara; Claus, Sandrine P.; Sanderson, Jeremy; Hudspith, Barry N.; Brostoff, Jonathan; Ward, Jane L.; Lovegrove, Alison; Shewry, Peter R.; Jones, Hannah E.; Whitley, Andrew M.; Gibson, Glenn R. (PloS one, 2014)
A variety of foods have been implicated in symptoms of patients with Irritable Bowel Syndrome (IBS) but wheat products are most frequently cited by patients as a trigger. Our aim was to investigate the effects of breads, which were fermented for different lengths of time, on the colonic microbiota using in vitro batch culture experiments. A set of in vitro anaerobic culture systems were run over a period of 24 h using faeces from 3 different IBS donors (Rome Criteria-mainly constipated) and 3 healthy donors. Changes in gut microbiota during a time course were identified by fluorescence in situ hybridisation (FISH), whilst the small-molecular weight metabolomic profile was determined by NMR analysis. Gas production was separately investigated in non pH-controlled, 36 h batch culture experiments. Numbers of bifidobacteria were higher in healthy subjects compared to IBS donors. In addition, the healthy donors showed a significant increase in bifidobacteria (P<0.005) after 8 h of fermentation of a bread produced using a sourdough process (type C) compared to breads produced with commercial yeasted dough (type B) and no time fermentation (Chorleywood Breadmaking process) (type A). A significant decrease of δ-Proteobacteria and most Gemmatimonadetes species was observed after 24 h fermentation of type C bread in both IBS and healthy donors. In general, IBS donors showed higher rates of gas production compared to healthy donors. Rates of gas production for type A and conventional long fermentation (type B) breads were almost identical in IBS and healthy donors. Sourdough bread produced significantly lower cumulative gas after 15 h fermentation as compared to type A and B breads in IBS donors but not in the healthy controls. In conclusion, breads fermented by the traditional long fermentation and sourdough are less likely to lead to IBS symptoms compared to bread made using the Chorleywood Breadmaking Process.